Recurrent Cerebral Infarctions in Primary Sjögren Syndrome: A Case Report and Literature Review - Li, Jia-Ai; Meng, Hong-Mei; Cui, Zhi-Tao; Wang, Xue; Miao, Jing (Frontiers in Neurology, 2018)
Recurrent cerebral infarctions are extremely rare in patients with primary Sjögren syndrome. We report a 66-year-old woman who was admitted to our hospital due to acute cerebral infarction with exacerbation of dysphagia and right-sided hemiplegia as the main symptoms. In the past 3 months, she had developed cerebral infarction twice, even though she had no risk factors for atherosclerosis. She was eventually diagnosed with primary Sjögren syndrome based on a long history of dryness of the eyes and mouth, positive anti-Ro(SSA) antibodies, and the findings of a labial salivary gland biopsy. The response to pulse methylprednisolone therapy after recurrent cerebral infarctions was poor. Thus we consider primary Sjögren syndrome patients with central nervous system involvement should be treated as soon as possible.